O Mosaico Literário em O Amanuense Belmiro - Célia Tamura (Revista Criação & Crítica, 2009)
This paper analyses the literary sources used by Cyro dos Anjos (1906-1994) for composing the novel O amanuense Belmiro (1937), revealing them as one of the Quixotesque’s literary modalities. As a man of a vast reading, the protagonist Belmiro evokes, at each moment, a literary work or its fragment, as well as childhood’s song and fabulous myth.